2014
DOI: 10.1088/0004-637x/781/2/60
|View full text |Cite
|
Sign up to set email alerts
|

ONE HUNDRED FIRST STARS: PROTOSTELLAR EVOLUTION AND THE FINAL MASSES

Abstract: We perform a large set of radiation hydrodynamics simulations of primordial star formation in a fully cosmological context. a Our statistical sample of 100 First Stars show that the first generation of stars have a wide mass distribution M popIII = 10 ∼ 1000 M ⊙ . We first run cosmological simulations to generate a set of primordial star-forming gas clouds. We then follow protostar formation in each gas cloud and the subsequent protostellar evolution until the gas mass accretion onto the protostar is halted by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

41
625
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 564 publications
(670 citation statements)
references
References 88 publications
41
625
3
1
Order By: Relevance
“…In the "PopIII star remnants" scenario, BHs are predicted to form in mini-haloes (M h ≈ 10 5 M ) with gas below a critical metallicity (Z < 10 −3.5 Z , Bromm et al 2001;Schneider et al 2002) at redshift z = 30 − 20 from the remnants of the first generation of stars (PopIII, Madau & Rees 2001;Volonteri, Madau & Haardt 2003). Observational evidence on the initial mass function (IMF) of PopIII stars are lacking, but theoretical studies suggest that they could have masses in the range 10 − 1000 M (Bromm & Yoshida 2011;Hirano et al 2014). A massive star M 260M can lead to the formation of a BH seed of ≈ 100 M (Fryer, Woosley & Heger 2001), retaining half the mass of the star.…”
Section: Introductionmentioning
confidence: 99%
“…In the "PopIII star remnants" scenario, BHs are predicted to form in mini-haloes (M h ≈ 10 5 M ) with gas below a critical metallicity (Z < 10 −3.5 Z , Bromm et al 2001;Schneider et al 2002) at redshift z = 30 − 20 from the remnants of the first generation of stars (PopIII, Madau & Rees 2001;Volonteri, Madau & Haardt 2003). Observational evidence on the initial mass function (IMF) of PopIII stars are lacking, but theoretical studies suggest that they could have masses in the range 10 − 1000 M (Bromm & Yoshida 2011;Hirano et al 2014). A massive star M 260M can lead to the formation of a BH seed of ≈ 100 M (Fryer, Woosley & Heger 2001), retaining half the mass of the star.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, statistical studies are needed to study the overall mass distribution of primordial stars. Our previous work (Hirano et al 2014, hereafter Paper I) achieves this goal with more than one hundred cosmological samples of primordial star-forming clouds. We first follow the early evolution until the formation of the protostellar core with three-dimensional (3D) cosmological simulations.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent simulations found that the protostellar disk forming in the minihalo fragments into multiple clumps (Clark et al 2011;Greif et al 2012;Stacy et al 2012;Latif et al 2013b; and leads to the formation of multiple stars. In the case of a single star per halo, they may still reach up to a thousand solar masses at z=25 (Hirano et al 2014), but feedback from the black hole itself shuts its own accretion and limits its growth (Johnson & Bromm 2007;Alvarez et al 2009). Perhaps, as suggested by Madau et al (2014), they may still grow under prolonged episodes of super-Eddington accretion.…”
Section: Introductionmentioning
confidence: 99%